Legal protection against the existence of "Wetu Telu" traditional society against law number 11/2020 concerning work creation (omnibus law) - Rahman, Irham; Bramantyo, Rizki Yudha (International research journal of management, IT and social sciences, 2020)
The Wetu Telu indigenous people in Bayan, North Lombok have the traditions of their ancestors that have Islamic nuances and their existence is recognized until now. The existence of indigenous peoples has been recognized and respected by the 1945 Constitution. However, the existence of new laws and regulations on indigenous peoples has again encountered problems that threaten their existence. The Omnibus Law which was recently passed is considered to provide a legal loophole that could displace the existence of indigenous peoples. The purpose of this research is to find out the legal problems of the threat to the existence of the Wetu Telu indigenous people and to know the concept of the Work Creation Act (Omnibus Law) in Bayan Village, North Lombok Regency, West Nusa Tenggara. This research uses juridical empirical or socio-legal research, which is a type of sociological legal research or field research that examines applicable legal provisions. The results of this study show that the normative issue of the Omnibus Law can lead to norm conflicts with other laws regarding the recognition of indigenous peoples in Indonesia.